Patrones mamográficos durante el tamizaje de cáncer de mama en mujeres - Apolo Sigcho, Helen Doménica (Machala : Universidad Técnica de Machala, 2023)
INTRODUCTION: Breast cancer is one of the malignant tumors that is positioned as the second most frequent cause of death worldwide in terms of prevalence and mortality. Through mammographic screening, we try to reduce the statistics by applying it according to the risk in women, therefore the interpretation of mammography patterns according to their malignancy is standardized by BI-RADS categories being essential for the communication of the results between health professionals, which is kept current and constantly updated. OBJECTIVE: To describe the main mammographic patterns that are visualized in breast cancer screening in women through the search of articles in scientific databases to facilitate the correct interpretation by health personnel. METHODOLOGY: This is a descriptive and retrospective study through literature review, based on scientific articles obtained from certified online sites with academic content extracted from PUBMED, GOOGLE ACADEMIC AND COCHRANE databases, official WHO/PAHO sources and Ecuadorian guidelines corresponding to the last five years with quartile 1 and 2.
INTRODUCCIÓN: El cáncer de seno pertenece a las neoplasias malignas que se posiciona como la segunda causa de muerte a nivel mundial más frecuentes en prevalencia como mortalidad a nivel mundial. A través del tamizaje por cribado mamográfico se intenta reducir las estadísticas aplicándose según el riesgo en la mujer, por ello la interpretación de los patrones en la mamografía según su malignidad se ve estandarizada por categorías BI-RADS siendo esencial para la comunicación de los resultados entre profesionales de salud, la misma que se mantiene vigente y en constante actualización. OBJETIVO: Describir los principales patrones mamográficos que se visualizan durante el cribado de cáncer de mama en mujeres a través de la búsqueda de artículos en base de datos científicos para facilitar la interpretación correcta por el personal de salud. METODOLOGÍA: Es un análisis descriptivo y retrospectivo a través de revisión bibliográfica, basada en 21 artículos científicos obtenidos de sitios online certificados con contenido académico correspondientes a los últimos cinco años con cuartil 1 y 2 extraídos desde la base de datos PUBMED, GOOGLE ACADÉMICO Y COCHRANE, fuentes oficiales OMS/OPS y guías del Ecuador.
Keywords: CANCER DE MAMA; MAMOGRAFIA; BI-RADS; TAMIZAJE